DETECTION OF CEREBRAL ATROPHY IN TYPE- II DIABETES MELLITUS BY MAGNETIC RESONANCE IMAGING OF BRAIN - Khan, Ghayyur; Khan, Nasir; Aziz, Abdul (Journal of Ayub Medical College Abbottabad, 2010)
Background: Diabetes is a metabolic disorder that affects many systems in the body. Cerebral atrophy is one of the complications of diabetes and research is on going to find out its aetiopathological factors. The main aim of the study was to determine the frequency of cerebral atrophy in type-II diabetes mellitus using magnetic resonance imaging of the brain. Methods: One hundred diabetic patients (Random blood sugar >126 mg/dl) were recruited in this study after the informed consent from every patient. Duration of diabetes was five years and more in all the patients as determined by their glycosylated haemoglobin which was >6 in all the patients. All the patients were undergone MRI of brain using 1.5 Tesla power magnetic resonance imaging machine of Picker Company. Evan’s index, a specific parameter for measurement of cerebral atrophy was calculated on MR images and was used in this study. Results: In male group the frequency of cerebral atrophy was 22 (47%) and in female group it was found to be 23 (43%). When we study the overall population the frequency was found to be 45 (45%). The results are well in concordance with the previous data published on this issue. Conclusions: Cerebral atrophy, a complication of long standing diabetes is quite frequent in our population and is well diagnosed by MRI. Keywords: Diabetes Mellitus, cerebral atrophy, MRI, frequency, complications of diabetes